Kdo jsou dnešní Austrálci? Pojetí ženství, rodiny a spirituality - Jana Kulhánková (AntropoWebzin, 2009)
The following study discusses contemporary urban Aboriginal culture. It addresses principles of women’s Indigenous Family Care centre in Australia, where the author volunteered, and maintained an ethnographic research. This organisation, Kummara, is based on family care, strengthening of women’s business, and reconnecting Aboriginal women to their cultural role. In fact, the Aboriginal women practicing family care and women’s spirituality in Kummara contribute to revitalisation of traditional Indigenous culture. This occurs mainly in education of children and young people (implementing rites of passage and parental programs), and in reconnecting to the traditional role of women in family, community and in spiritual life. In the Aboriginal context of health, the women in Kummara engage in a process of cultural, spiritual and emotional healing. They have adapted their ways of doing this to modern society and have been influenced by different Western and other cultural concepts while still trying to preserve elements of their ‘traditional’ past. By drawing from different cultural notions and contemporary cultural concepts, the process of revitalising leads to by o  means interesting modern notion of Aboriginal culture.